Blockchain Is Top Skill For 2020 - Mohammed, Datu; Aisha, Nur; Himki, Arzo; Dithi, Arusyi; Ardianto, Agung Yudo (Pandawan, 2020)
This research aims to learn why Blockchain Technology can be the most demanding hard skills in companies in 2020 as quoted from LinkedIn and the positive impact that Blockchain Technology has on a company. If we see, at this time usually requires at least a third party to make a transaction, and a company usually only stores data / information on a centralized server which makes the data easy to hack. From this case, Blockchain technology can be used as a way out for a company to make data / information not easy to be hacked. Because, Blockchain uses a distributed server system that is validated, which makes Blockchain safer from evil parties who want to hack information, and Blockchain has other advantages such as more cost-effective, better transparency and traceability. Therefore Blockchain Technology is a particular attraction for a company and is the hard skill most demanded by the company in 2020.